Handel - Burrows, Donald 1945- (The master musicians, 2012)
Handel's compositions form one of the peaks of creative achievement in the Baroque period, and cover a remarkable range. His compositional processes were often complex, but could result in accessible and memorable 'hit tunes'. This biography provides an account of the man and his music. This new edition incorporates new material, informed by wide experience of modern performances of Handel's music, including the revival of his operas and experimentation with 'authentic' performance practices.